Psychomotor performances relevant for driving under the combined effect of ethanol and synthetic cannabinoids: A systematic review - Giorgetti, Arianna; Orazietti, Vasco; Busardò, Francesco Paolo; Giorgetti, Raffaele (Frontiers in Psychiatry, 2023)
Objective To determine whether the acute co-consumption of ethanol and synthetic cannabinoids (SCs) increases the risk of a motor vehicle collision and affects the psychomotor performances relevant for driving. Design Systematic review of the literature. Data sources Electronic searches were performed in two databases, unrestricted by year, with previously set method and criteria. Search, inclusion and data extraction were performed by two blind authors. Results Twenty articles were included, amounting to 31 cases of SCs-ethanol co-consumption. The impairment of psychomotor functions varied widely between studies, ranging from no reported disabilities to severe unconsciousness. Overall, a dose-effect relationship could not be observed. Conclusion Despite the biases and limitations of the literature studies, it seems likely that the co-consumption poses an increased risk for driving. The drugs might exert a synergistic effect on the central nervous system depression, as well as on aggressiveness and mood alterations. However, more research is needed on the topic.